A Rare Earth Oxides-Containing Internal Reference Material of Purified Monazite from Bangka Island - Ronaldo Irzon; Agus Didit Haryanto; Kurnia Miharja (BRIN, 2022)
Monazite mineral contains a sufficient composition of rare earth elements which are currently required widely in modern industries. Reference materials are needed to validate the measurement results, including the rare earth elements analysis. This study presents the processing of purified monazite from the PT Timah Metallurgical Unit in Muntok to become low-cost and rare earth oxides-containing internal reference material. Eight X-ray fluorescence measurements of four splits of the monazite were done for precision test and to establish its information values. The high CeO2 and LaO2 composition (>10%) implies the economic worth of the studied sample. Based on the acceptance criteria of RSDexperimental <10%, RSDexperimental ?66%xCVHorwitz, and Horrat <2, the concentration of fourteen analytes is acceptable to be set as information values. The studied monazite content resembles the other purified one of Myanmar. Its much lower phosphate composition signifies that the sample is more precious than refined monazites from Iran and Australia. Keyword: Monazite, Internal reference material, XRF, REE.